Probiotic containing Lactobacillus reuteri DSM 17648 as an adjunct treatment for Helicobacter pylori infection: A randomized, double-blind, placebo-controlled trial - Nur Izreena, Ismail; Khairul Najmi, Muhammad Nawawi; Chew, Deborah Chia Hsin; Kok, Wei Hao; Nik Ritza, Kosai Nik Mahmood; Lee, Gary Chong Chearn; Wong, Zhiqin; Azmi, Mohd Tamil; Joseph, Hazel; Raja Affendi, Raja Ali * (Wiley, 2023)
Background: Despite multiple therapy regimens, the decline in the Helicobacter pylori eradication rate poses a significant challenge to the medical community. Adding Lactobacillus reuteri probiotic as an adjunct treatment has shown some promising results. This study aims to investigate the efficacy of Lactobacillus reuteri DSM 17648 in H. pylori eradication and its effect in ameliorating gastrointestinal symptoms and adverse treatment effects.